Inside social enterprise : looking to the future - Fitzhugh, Helen, ....- (Policy Press : Bristol, 2015)
Social enterprises - real businesses that trade for a social purpose - are a growing phenomena with an increasing role to play in society, but there is widespread confusion and controversy over the definition of the term. This exciting book includes nearly forty interviews with the most influential and experienced social enterprise practitioners, supporters, thinkers and policy makers. In their own words, they discuss their organisations, values and world-changing goals, providing fresh clarity and understanding on the real value of social enterprises. Jargon-free, the book delivers a lively and clear introduction as to what social enterprises are, how they can change individual lives and, by challenging assumptions, may even offer new directions for the future of capitalism. It is a unique guide for aspiring practitioners, students, researchers and public sector staff.
Keywords: Ethisch ondernemen; Sociaal ondernemen